Lymphadenectomy in the treatment of sarcomas – indications and technique - Dunaj, Piotr; Żukowska, Ewa; Czarnecka, Anna M.; Krotewicz, Maria; Borkowska, Aneta; Chmiel, Paulina; Świtaj, Tomasz; Rutkowski, Piotr (Oncology Reviews, 2024)
Sarcomas are a rare type of malignancy with limited treatment options so far. This analysis aimed to describe the impact of lymphadenectomy on treating sarcoma patients. Sarcomas characterized by lymphatic spread are rare. For this reason, lymphadenectomy is not a procedure that is performed frequently. However, there are histological subtypes that spread more frequently through lymphatic vessels, such as rhabdomyosarcoma (RMS), epithelioid sarcoma (ES), clear cell sarcoma (CCS), and angiosarcoma. On the other hand, synovial sarcoma (SS) is not characterized by an increased tendency to lymphogenous metastases. In our study, we focus on these subtypes of sarcomas. The relationship between lymphadenectomy results and the subsequent prognosis of the patients was investigated. Metastases in the lymph nodes are diagnosed synchronously with distant metastases or when the primary tumor is detected. At the same time, despite lymphadenectomy, sarcoma patients developed further distant metastases. Currently, lymphadenectomy is not a routinely recommended method of treatment for patients with sarcomas. Most often, its potential use is indicated in the case of epithelioid sarcoma, clear cell sarcoma, and rhabdomyosarcoma after a previous positive sentinel lymph node biopsy (SLNB) result. Multicenter randomized prospective clinical trials on the role of lymphadenectomy in the treatment of sarcomas are needed.